Experimental study of settlement and migration patterns of proppant in long narrow fractures in deep shale - LIU Haoqi, CHEN Fuhong, YU Zhili, GONG Wei, LUO Xi, LIN Hun (Youqicang pingjia yu kaifa)
Shale gas, an unconventional natural gas resource, has become an important supplement to global conventional oil and gas resources. With the increasing development of shale gas resources, deep shale gas reservoirs have emerged as key targets for exploration and production. These reservoirs are characterized by complex geological structures, high rock plasticity, and significant vertical and horizontal stress differences. Such conditions hinder the formation of complex fracture networks during hydraulic fracturing, often resulting in simple, narrow, and long fractures. The narrow width of these fractures significantly affects the settlement and migration of proppants, which in turn influences fracture conductivity and determines the effectiveness of reservoir stimulation. Therefore, investigating the settlement and migration behaviors of proppants in long narrow fractures is essential for the safe and efficient production of deep shale gas wells. Current experimental studies on proppant migration commonly use parallel-plate simulation devices made of organic glass. Research indicates that proppant settlement and migration are substantially influenced by viscous fluid drag, with the drag coefficient depending on factors such as particle shape, concentration, and flow rate. Additionally, proppant type, density, and concentration further affect proppant distribution. However, most existing studies are based on the fracture geometries of medium and shallow shale reservoirs, which differ from those of deep shale formations in both fracture width and suitable proppant size. To address this gap, this study employed a large-scale visualized simulation device to examine the settlement and migration of proppants in long narrow fractures in deep shales. The objective is to clarify the effects of different proppant properties and fracturing parameters on proppant distribution, thereby providing theoretical support for fracturing stimulation in deep shale reservoirs. The experimental setup included a fracture simulation device, a mixing unit, and a circulation system. The fracture simulation device was composed of interconnected organic glass plates, with adjustable fracture widths between 2-3 mm to replicate the fractures in deep shale. Slickwater fracturing fluids were prepared with three viscosities: 3 mPa·s, 6 mPa·s, and 9 mPa·s. Selected proppants included 40/70 mesh, 70/140 mesh, and 100/200 mesh quartz sand, along with 70/140 mesh coated ceramic proppants, representing micro-sized particles. A total of 11 experimental groups were designed to investigate the effects of fracturing fluid viscosity, injection rate, proppant concentration, proppant particle size, proppant type, and fracture width variation. Experimental results indicated that, compared with the wider fractures of medium and shallow shales, under the same conditions, long narrow fractures in deep shale promote the agglomeration of proppant particles, causing a rapid settlement near the inlet. This led to a reduced leading-edge slope of the sand bank and a smaller height difference between the front and rear of the sand bank compared to wider fractures. The overall proppant distribution tends to be more uniform and smoother. In long narrow fractures of deep shale, the proportion of terminal sand bank area to the total sand bank area increases with higher fracturing fluid viscosity and injection rate, while the effect of proppant concentration is relatively limited. Micro-sized proppants are more prone to settling at the far end of the narrow fracture and contribute to a more uniform overall distribution. Moreover, the contraction of fracture width has no significant effect on sand bank placement before contraction, but it hinders the flow and placement of proppant particles after contraction, resulting in decreased proppant settlement. Due to the high closure pressure in deep shale reservoirs, fractures are prone to closure, and the reduction in proppant settlement after fracture contraction further increases the difficulty of effective fracture support. This experimental study reveals the settlement and migration patterns of proppants in long narrow fractures in deep shale, providing a theoretical foundation for optimizing fracturing simulation strategies. The findings have practical significance for selecting proppant types and optimizing fracturing parameters to enhance the production efficiency of deep shale gas wells.